Transcranial Recording of Electrophysiological Neural Activity in the Rodent Brain in vivo Using Functional Photoacoustic Imaging of Near-Infrared Voltage-Sensitive Dye - Kang, Jeeun; Zhang, Haichong K.; Kadam, Shilpa D.; Fedorko, Julie; Valentine, Heather; Malla, Adarsha P.; Yan, Ping; Harraz, Maged M.; Kang, Jin U.; Rahmim, Arman; Gjedde, Albert; Loew, Leslie M.; et al. (Frontiers in Neuroscience, 2019)
Minimally-invasive monitoring of electrophysiological neural activities in real-time—that enables quantification of neural functions without a need for invasive craniotomy and the longer time constants of fMRI and PET—presents a very challenging yet significant task for neuroimaging. In this paper, we present in vivo functional PA (fPA) imaging of chemoconvulsant rat seizure model with intact scalp using a fluorescence quenching-based cyanine voltage-sensitive dye (VSD) characterized by a lipid vesicle model mimicking different levels of membrane potential variation. The framework also involves use of a near-infrared VSD delivered through the blood-brain barrier (BBB), opened by pharmacological modulation of adenosine receptor signaling. Our normalized time-frequency analysis presented in vivo VSD response in the seizure group significantly distinguishable from those of the control groups at sub-mm spatial resolution. Electroencephalogram (EEG) recording confirmed the changes of severity and frequency of brain activities, induced by chemoconvulsant seizures of the rat brain. The findings demonstrate that the near-infrared fPA VSD imaging is a promising tool for in vivo recording of brain activities through intact scalp, which would pave a way to its future translation.